ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MEDIATING DI LINGKUNGAN DINAS PENATAAN RUANG DAN PEMUKIMAN PROVINSI SUMATERA UTARA - Putri Kemala Dewi (Jurnal Riset Akuntansi dan Bisnis, 2012)
The measurement of performance is an assessment process of work progress toward the determined target. The measurement of performance is management device to increase the quality of decision making and accountability. Employees' good performance will directly influence the performance of their institution, and improving employees’ performance will take a long time and a long process. The aim of this study was to verify some factors which influenced employees’ performance with motivation as the mediating variable in the Layout and Settlement Service of North Sumatera Province. The research was explanatory research type. The data comprised of the primary data and were gathered by using questionnaires. The hypothesis was tested by using Structural Equation Modeling (SEM), using an Amos version 18 program. The samples comprised of 150 employees, using purposive sampling and proportionate stratified random sampling technique. The result of the research showed that leadership had negative influence on employees’ motivation and performance. Communication had positive influence on employees' motivation and performance. Organization climate had positive influence on employees' motivation and performance. Work discipline had positive influence on employees' motivation and performance. Motivation as the mediating variable had negative influence on employees’ performance.